MODEL GERAK DASAR BERBASIS MULTIMEDIA INTERAKTIF TERHADAP KETERAMPILAN GERAK DASAR SISWA SEKOLAH DASAR - M. Fahri Arridho; Nurkadri Nurkadri; Mufti Abdillah; Chrystian Rambe; Josafat Franata L. Sormin; Fatimah Zahra Wardani (Riyadhoh : Jurnal Pendidikan Olahraga, 2023)
The purpose of this study is to determine how well elementary school students are influenced by interactive multimedia-based basic motion models. An experiment with a one-group pre-test-post-test design was used for the research. The example of this exploration is 1st grade primary school understudies. The outcomes during the pre-test with a typical worth of 184.55 while the consequences of the typical post-test score were 265.425 intending that there was an increment of 44%. The t-count value is 42.389 and the t-table value is 1.685 in the significance test of the difference, indicating that there is a significant difference between the two groups before and after receiving an interactive multimedia-based basic motion model. According to this data, elementary school students are significantly influenced by the basic motion model.